Further Characterization of Human Platelet Activation in the Absence of Aggregation: Phosphorylations of Specific Proteins and Relationship with Platelet Secretion - Nunez, Danièle; Levy-Toledano, Sylviane (Thrombosis and Haemostasis, 1984)
Platelet aggregation and secretion have been described to be associated with phosphorylation reactions. Thrombasthénie and EDTA-treated control platelets undergo a normal serotonin release in the absence of aggregation. We now studied the phosphorylation of specific proteins associated with platelet secretion. In the presence of ionophore, significant increases occurred in the phosphorylation of two polypeptides of 43,000 and 20,000 molecular weight (P43 and P20) in a concentration dependent manner, and this was accompanied by an increase in the 14C-5HT release. The 32P-labelling of P43 and P20 reaches a peak within 1 min of platelet activation and is followed by a rapid dephosphorylation over the next 2-10 min. While the P20 is identified as the myosin light chain, the identity and the function of the P43 remain unknown.Isoelectric focusing separates 4 proteins from P43 during two dimensional electrophoresis, but only one of them is phosphorylated by A 23187. Chlorpromazine (CPZ) and trifluoperazine (TFP) inhibit the P43 and P20 phosphorylation as well as the 14C- 5HT release in a dose dependent manner. The inhibitory action of the drugs is more pronounced for P43 than for P20, especially when the reactions are carried out at 20° C instead of at 37° C, while the release reaction is still inhibited under these conditions. These results allow different hypotheses for the relationship of phosphorylation-secretion and indicate the importance of one of these proteins (P43) for the release reaction.
Keywords: Phosphorylation; Ionophore secretion; Phenothiazines